Postpartum depression biomarkers predict exacerbation of OCD symptoms during pregnancy. (November 2020) - Kaminsky, Zachary A.; Osborne, Lauren M.; Guglielmi, Valeria; Jones, Ilenna; Grenier, Winston; Clark, Karen; Ross, Evelyn; Meilman, Samantha; Nestadt, Paul; Payne, Jennifer L.; Samuels, Jack; Nestadt, Gerald
Highlights: Epigenetic biomarkers of postpartum depression, HP1BP3 and TTC9B, predict exacerbation of OCD symptoms during pregnancy. A methylome wide approach identifies MS4A7 as a DNA methylation proxy of the ratio of monocytes to non-monocytes. Incorporation of MS4A7 into the prediction model improves OCD symptom exacerbation prediction to 75%.